PENGARUH BRAND IMAGE, VIRAL MARKETING, DAN BRAND TRUST TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI FINTECH (Studi Kasus pada Mahasiswa Universitas Muhammadiyah Surakarta) - Sekar Ade Dyah Wirawati; Yuli Tri Cahyono (JURNAL ILMIAH EDUNOMIKA, 2025)
In the industry 4.0 era, digital wallets and financial technology (fintech) are growing rapidly and are supported by government regulations, especially OJK. A positive brand image strengthens the perception of reliability and security of the app, while viral marketing leverages the power of social media to expand reach and increase brand awareness. On the other hand, brand trust is a key determinant in building consumer loyalty because it involves data security and transaction convenience. The integration of these three aspects is considered important for fintech app managers to attract, retain, and increase user loyalty in a competitive market. This study aims to analyze the effect of brand image, viral marketing, brand trust on the decision to use fintech aplication. This study uses quantitative research methods. The results of this study are viral marketing and brand trust affect the decision to use the fintech application while Image has not.